The Investıgatıon Of The Effect Of Early Treatment Procedures In Maxıllary Development In Unılateral Comple Cleft Lıp And Palate - Selam Al-K; Erdal Işıksal; Servet Doğan (Galenos Yayinevi, 2004)
Cleft lip and palate are the most common craniofacial deformities. The urgent need to understand more fully these mechanisms is underlined by the fact that the incidence of cleft lip and palate is increasing alarmingly, having almost doubled in the past 25 years.The study is performed to investigate the effect of early treatment approaches on maxillary growth. Our study examines the changes in maxillary dimensions in 17 unilateral complete cleft lip and palate babies from birth up to the time of surgery at age 9 month comparing them with 8 normal babies.We applied lip surgery at the end of the third month and maxillary orthopedic treatment from birth on 10 unilateral complete cleft lip and palate babies called first group,and we applied lip surgery after birth within fifteen days and maxillary orthopedic treatment from birth on 7 unilateral complete cleft lip and palate babies called second group. Measurements of width and length from models taken from babies were evaluated 3- dimensionally and analysed statistically.We compared three groups and early and late lip surgery groups with the help of varyans analyses (one step,kovaryans and split plot).After evaluating varyans analyses, we compared means of the groups with the help of Duncan tests.We evaluated early and late groups with the help of student t test. The results of this study revealed that lip surgery effects the anterior-posterior dimensions of the cleft-ed maxilla, but has no effect on the transversal dimensions related to the use of presurgical orthopedic appliances which prevent a collapse of the maxillary arch. Finally, the time of lip surgery is not important in regard to maxillary growth and the physical state of the baby could be used as a determinant factor in this decision.